Strategi Penguatan Keunggulan Program Studi Tata Boga degan Metode SWOT dan QSPM: Studi Kasus Prodi D3 Tata Boga Politeknik Negeri Balikpapan - Andi Yasir Amsal; Tuatul Mahfud; Hartini Ramli (Syntax Corporation Indonesia, 2025)
Strengthening the excellence of study programs is a strategic step in order to improve the quality of competitiveness of study programs in order to be able to adapt to the needs of scientific developments at the global level. Therefore, a comprehensive and data-based strategy formulation is needed to optimize the Strengthening process. This study aims to identify the Strengths, opportunities, Weaknesses, and Threats and formulate a strategy to Strengthen the excellence of the D3 Culinary Arts Study Program of Balikpapan State Polytechnic. The methods used in formulating this excellence Strengthening strategy are SWOT and QSPM. The results obtained in this study are based on the IE matrix which is seen in the total IFEM score of 2,966 and EFEM of 2,924 in the SWOT matrix, the position of the Study Program is in quadrant V (Hold and Maintain) which means it has moderate internal and external capabilities so that it is necessary to Strengthen the Strength variables and develop according to the opportunities it has. Based on the QSPM analysis, alternative strategies to utilize industry-based curriculum and the implementation of PBL-based curriculum to establish collaboration with institutions and industries at national and international levels to improve student competency and internship opportunities (9.90), overcome the community paradigm towards universities in Java which are considered better by improving international accreditation of study programs and utilizing a wide alumni network for promotion and branding, (9.84) and utilizing a wide alumni network to expand cooperation and funding in the fields of education and research and improving mentoring and networking programs for students (9.82) are the three priorities of the Study Program